Differential diagnosis of basal cell carcinoma by high‐resolution ultrasound elastography. Issue 2 (15th January 2022) - Han, Xiaohua; Li, Jiyou; Zeng, Fuqiang; Liu, Hongmei; He, Yanni
Abstract: The aim of this study was to assess the value of high‐resolution ultrasonic quantitative parameters of shear wave elastography (SWE) in basal cell carcinoma (BCC). A total of 86 cases of BCC were enrolled as the case group, and 38 other similar skin pigmented lesions were randomly selected as the control group. Using pathological results as the gold standard, the diagnostic test method was used to evaluate the ability of high‐frequency ultrasonic elastography to diagnose BCC, and the 2D ultrasonographic features, blood flow image characteristics, and SWE of BCC were summarized.